2015
DOI: 10.1007/s12539-015-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

Implying Analytic Measures for Unravelling Rheumatoid Arthritis Significant Proteins Through Drug–Target Interaction

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune and inflammatory disease that mainly alters the synovial joints and ultimately leads to their destruction. The involvement of the immune system and its related cells is a basic trademark of autoimmune-associated diseases. The present work focuses on network analysis and its functional characterization to predict novel targets for RA. The interactive model called as rheumatoid arthritis drug-target-protein (RA-DTP) is built of 1727 nodes and 7954 edges followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In a recent study, HSP90AA1 was suggested as a pathogenesis‐related protein of RA by network analysis and its functional characterization method , which is first validated in this study by the real‐world clinical subjects that the prevalence of anti‐HSP90AA1 antibodies in patients with RA was higher than that in healthy controls, further proving that network approaches combined with valid functional information interpretation can be a powerful tool to predict new biomarker candidates of diseases.…”
Section: Discussionsupporting
confidence: 52%
“…In a recent study, HSP90AA1 was suggested as a pathogenesis‐related protein of RA by network analysis and its functional characterization method , which is first validated in this study by the real‐world clinical subjects that the prevalence of anti‐HSP90AA1 antibodies in patients with RA was higher than that in healthy controls, further proving that network approaches combined with valid functional information interpretation can be a powerful tool to predict new biomarker candidates of diseases.…”
Section: Discussionsupporting
confidence: 52%
“…A previous study found that KNG1 overexpression exacerbated oxidative stress and mitochondrial damage ( 62 ). Singh et al ( 63 ) predicted that KNG1 may be the potential target of RA by bioinformatics, which requires further experimental verification. The level of GPNMB is low in normal hepatocytes but higher in hepatocellular carcinoma cells according to research ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, there has been a tremendous increase in the in-silico structure prediction of protein using different software and algorithms. 12 International Journal of Pharmaceutical Investigation, Vol 9, Issue 2, Apr-Jun, 2019 But the accuracy of the structure prediction, the magnitude of errors in the fold assignment, modelling of side chains and loops still need a considerable body shift. Aquaporin-9s are a family of proteins encoded by AQP9 gene in humans.…”
Section: Discussionmentioning
confidence: 99%